2010
DOI: 10.2209/tdcpublication.51.77
|View full text |Cite
|
Sign up to set email alerts
|

Dental Erosion in Workers Exposed to Sulfuric Acid in Lead Storage Battery Manufacturing Facility

Abstract: Dental erosion, and specifically its symptoms, has long been studied in Japan as an occupational dental disease. However, in recent years, few studies have investigated the development of this disease or labor hygiene management aimed at its prevention. As a result, interest in dental erosion is comparatively low, even among dental professionals. Our investigation at a lead storage battery factory in 1991 found that the work environmental sulfuric acid density was above the tolerable range (1.0mg/m 3 ) and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 5 publications
2
19
0
8
Order By: Relevance
“…In an earlier study, we reported that cadmium concentrations in the saliva and mouth rinse of employees working with cadmium had a high correlation with the work environment, and that mouth rinse could be used as an index for individual exposure 17) . In our earlier study 18) , sulfuric ion concentrations in mouth rinse obtained from employees working with sulfuric acid were approximately twice those of employees not working with sulfuric acid. The average sulfuric ion concentration in the work environment of the battery-charging area of the plant was approximately double that of the other work environments investigated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In an earlier study, we reported that cadmium concentrations in the saliva and mouth rinse of employees working with cadmium had a high correlation with the work environment, and that mouth rinse could be used as an index for individual exposure 17) . In our earlier study 18) , sulfuric ion concentrations in mouth rinse obtained from employees working with sulfuric acid were approximately twice those of employees not working with sulfuric acid. The average sulfuric ion concentration in the work environment of the battery-charging area of the plant was approximately double that of the other work environments investigated.…”
Section: Discussionmentioning
confidence: 66%
“…However, in a lead storage battery factory where dental erosion had been identified in the past, local sulfuric ion concentration in the work environment was found to be above the maximum permissible concentration (1.0 mg/m 3 ) 18) . Therefore, in our previous study 18) , workers handling sulfuric acid were given an oral examination and rates of dental erosion by tooth type, number of working years and sulfuric acid density in the work environment investigated. Where dental erosion was diagnosed, the degree for each case was identified according to a diagnostic criterion.…”
Section: Introductionmentioning
confidence: 92%
“…Suyama et al, 17,18 verificaram maior concentração de erosão nos dentes anteriores inferiores de profissionais expostos ao ácido sulfúrico. O mesmo grupo de pesquisadores publicou um estudo avaliando bochechos coletados de trabalhadores que lidam com este ácido a…”
Section: Discussionunclassified
“…12 Tais ácidos podem significar efeitos irritantes nos tecidos mucosos membranosos e epiteliais além de efeito químico corrosivo nos dentes, conhecido como erosão dental. 17,18 Algumas características clínicas representam a erosão dental causada por ácidos industriais e a diferem das causadas por alimentos ácidos e ácidos intrínsecos. O quadro 2 descreve detalhes que auxiliam o diagnóstico diferencial.…”
Section: Erosão Dental Ocupacionalunclassified
See 1 more Smart Citation